Novel heat recovery systems for building applications - Ahmad, Mardiana Idayu (2011)
The work presented in this thesis will explore the development of novel heat recovery systems coupled with low carbon technologies, and its integration to become one device with multifunction (building integrated heat recovery/cooling/air dehumidifier. In the first part of this thesis, an experimental performance of an individual heat recovery unit using Micro Heat and Mass Cycle Core (MHM3C) made of fibre papers with cross flow arrangement has been carried out. The unit was tested in an environmental control chamber to investigate the effects of various parameters on the performance of heat/energy recovery unit. The results showed that as the airflow rate and temperature change increase, the efficiency decreases whilst recovered energy increases. Integrating heat recovery system in energy-efficient system represents significant progress for building applications. As part of the research, the integration of heat recovery using a cross-flow fixed-plate with wind-catcher and cellulose fibre papers of evaporative cooling units have allowed part of the energy to be recovered with the efficiency of heat recovery unit ranged from 50 to 70%, cooling efficiency ranged from 31 to 54%.